MORPHOLOGICAL CONDITION OF THE MUCOUS DURING THE PERIOD OF PHYSIOLOGICAL CHANGE OF THE CANINES OF THE UPPER JAW - M. Cholovskyi (Український стоматологічний альманах)
Physiological eruption of teeth indicates the proper development of the child. According to modern literature, in many countries around the world there is an increase in the frequency of dental anomalies with a violation of the eruption of teeth. Influence on the child's body of negative factors of both local and general nature causes the formation of this orthodontic. It is scientifically substantiated that there is a strong correlation between the number of erupted teeth – maxilaris anomalies. This means that the greater the prevalence of orthodontic pathology, the fewer erupted permanent teeth.